2018
DOI: 10.1093/jxb/ery258
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting SPL genes to improve maize plant architecture tailored for high-density planting

Abstract: Maize (Zea mays ssp. mays) is an agronomically important crop and also a classical genetic model for studying the regulation of plant architecture formation, which is a critical determinant of grain yield. Since the 1930s, increasing planting density has been a major contributing factor to the >7-fold increase in maize grain yield per unit land area in the USA, which is accompanied by breeding and utilization of cultivars characterized by high-density-tolerant plant architecture, including decreased ear height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 115 publications
0
49
0
1
Order By: Relevance
“…However, high-density planting would cause a decline in R/FR ratios and trigger SAS, which is detrimental to biomass and seed yield of crops (Vandenbussche et al, 2005;Franklin, 2008). Earlier studies have documented a role of the phytochromes, PIFs, and the SPL gene family in regulating SAS in maize and related grass species (Whipple et al, 2011;Gonzá lez-Grandío et al, 2017;Wei et al, 2018). For example, recent studies suggest that the miR156-SPLs module also regulates MIR172 expression and flowering time in maize (Wu and Poethig, 2006;Chuck et al, 2007;Wu et al, 2009;Poethig, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high-density planting would cause a decline in R/FR ratios and trigger SAS, which is detrimental to biomass and seed yield of crops (Vandenbussche et al, 2005;Franklin, 2008). Earlier studies have documented a role of the phytochromes, PIFs, and the SPL gene family in regulating SAS in maize and related grass species (Whipple et al, 2011;Gonzá lez-Grandío et al, 2017;Wei et al, 2018). For example, recent studies suggest that the miR156-SPLs module also regulates MIR172 expression and flowering time in maize (Wu and Poethig, 2006;Chuck et al, 2007;Wu et al, 2009;Poethig, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we recently showed that overexpression of several ZmPIF genes confers enhancement of the SAS in Arabidopsis and that CRISPR knockout of multiple ZmPIF genes results in severely suppressing mesocotyl elongation in dark-grown seedlings, and reducing responsiveness to simulated shade treatment (Wu et al, 2019). Moreover, a recent study showed that multiple flowering-related genes, including AP2, MADS-box, and SPL genes, are directly regulated by ectopic expression of maize Unbranched3 (UB3, ZmSPL30) in transgenic rice plants (Du et al, 2017;Wei et al, 2018). Despite this progress, the molecular mechanisms regulating SAS in cereal grasses have just started to be unraveled.…”
Section: Discussionmentioning
confidence: 99%
“…By investigating drought stress induced changes in maize small RNA accumulation (Lunardon, Forestan, Farinati, Axtell, & Varotto, ), we observed the upregulation of miR156, which is involved in floral transition in Arabidopsis as negative regulator of SQUAMOSA PROMOTER BINDING PROTEIN LIKE (SPL; Wu & Poethig, ). In maize, miRNA156 negatively regulates the expression of TSH4 , UB2 , and UB3 (Chuck et al, ; Chuck et al, ; Chuck, Meeley, Irish, Sakai, & Hake, ; Wei et al, ), three SPL floral regulators which expression is altered after drought stress. Moreover, SPL gene family has recently been reported to function as a molecular link between drought stress signaling and developmental signaling in maize (Mao et al, ; Miao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Wu & Poethig, 2006). In maize, miRNA156 negatively regulates the expression of TSH4, UB2, and UB3 (Chuck et al, 2010;Chuck et al, 2014;Chuck, Meeley, Irish, Sakai, & Hake, 2007;Wei et al, 2018), three SPL floral regulators which expression is altered after drought stress. Moreover, SPL gene family has recently been reported to function as a molecular link between drought stress signaling and developmental signaling in maize (Mao et al, 2016;Miao et al, 2017).…”
Section: Drought Stress Impacts On Flowering and Inflorescence Devementioning
confidence: 99%
“…Substantial evidence suggests that the MIR156-SPL (SQUA-MOSA PROMOTER BINDING PROTEIN-LIKE) module plays an important role in regulating diverse aspects of plant growth and development, ranging from vegetative to reproductive phase transition, branching, leaf development, flowering time, panicle/ tassel architecture, fruit ripening, fertility, lateral root development, and abiotic stress responses 12,13 . SPLs encode a family of plant-specific transcription factors that share a highly conserved DNA-binding domain, the SBP domain.…”
mentioning
confidence: 99%